Human mitochondrial ribosomes can switch structural tRNAs – but when and why?. Issue 12 (2nd December 2017) - Chrzanowska-Lightowlers, Zofia; Rorbach, Joanna; Minczuk, Michal
ABSTRACT: High resolution cryoEM of mammalian mitoribosomes revealed the unexpected presence of mitochondrially encoded tRNA as a structural component of mitochondrial large ribosomal subunit (mt-LSU). Our previously published data identified that only mitochondrial (mt-) tRNA Phe and mt-tRNA Val can be incorporated into mammalian mt-LSU and within an organism there is no evidence of tissue specific variation. When mt-tRNA Val is limiting, human mitoribosomes can integrate mt-tRNA Phe instead to generate a translationally competent monosome. Here we discuss the possible reasons for and consequences of the observed plasticity of the structural mt-tRNA integration. We also indicate potential direction for further research that could help our understanding of the mechanistic and evolutionary aspects of this unprecedented system.